Dakwah di Era Digital: Antara Edukasi Publik, Sensasi Viral, dan Krisis Etika - Rohman; Irfan (Pawarta: Journal of Communication and Da'wah, 2026)
This study aims to examine the dynamics of Islamic preaching ethics on social media by highlighting the tension between educational and popularity orientation. The preaching transformation to the digital space presents opportunities for wider dissemination, but at the same time poses risks of substance reduction, commodification of religion, and a shift in religious authority. The research focuses on how preachers and audiences negotiate the value of preaching in a competitive algorithmic ecosystem. A qualitative approach was used with three main techniques: analysis of da'wah video content on YouTube, TikTok, and Instagram; in-depth interviews with preachers and audiences; and virtual observation of digital interactions. Data validity maintained through sources and methods triangulation. The findings reveal that digital da’wah operates within a spectrum of education and popularity, where sensational content often deviates from ethical standards, audiences face ambiguity in assessing quality, and religious authority shifts from scholarly legitimacy to algorithm-driven popularity. Nevertheless, ethical practices can be maintained through creative adaptation strategies such as storytelling, visualization, and healthy interaction with audiences. The main contribution of this study is the development of an ethical framework for digital da’wah that is adaptive to algorithmic logic while preserving scholarly substance, thereby offering a new perspective for the study of Islamic preaching in the social media era. This study concludes that the ethics of Islamic preaching in the digital era are not merely a matter of right or wrong according to religious law, but rather a strategy of adaptation to the logic of virality. The main contribution of this research lies in the formulation of a relevant, critical, and operational ethical framework for digital da’wah, which can serve as a reference for preachers, audiences, and religious institutions in maintaining the integrity of preaching within the digital public sphere.